2019
DOI: 10.1140/epjp/i2019-12725-8
|View full text |Cite
|
Sign up to set email alerts
|

On the (un)effectiveness of proton boron capture in proton therapy

Abstract: We present calculations and simulations on the role of the p+ 11 B→3α reaction in proton therapy. This reaction has been recently suggested to be responsible for a decrease in the survival probability of tumor cells, when they are irradiated with low-energy protons. However, at the concentration levels typical of the proposed boron carrier (sodium borocaptate, Na 2 B 12 H 11 SH, in short BSH), i.e. less than 100 ppm, both calculations and Monte Carlo simulations suggest that the dose related to this reaction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 21 publications
4
34
1
Order By: Relevance
“…As it is shown, the tumor with 1.4 cm of diameter has been treated by the proton beam with spread energy from 45 MeV to 60 MeV for low depth position (SOBP from 1.6 cm to 3 cm) and 121 MeV to 130 MeV for the deepest position (SOBP from 10 cm to 11.3 cm). The calculated energy ranges and the corresponding Bragg's peaks illustrated in this figure have agreement with the other reported data 25,26,45 . In the following presented results, the Bragg's end position and the corresponding proton energy have been mention to represent the tumor's depth.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…As it is shown, the tumor with 1.4 cm of diameter has been treated by the proton beam with spread energy from 45 MeV to 60 MeV for low depth position (SOBP from 1.6 cm to 3 cm) and 121 MeV to 130 MeV for the deepest position (SOBP from 10 cm to 11.3 cm). The calculated energy ranges and the corresponding Bragg's peaks illustrated in this figure have agreement with the other reported data 25,26,45 . In the following presented results, the Bragg's end position and the corresponding proton energy have been mention to represent the tumor's depth.…”
Section: Resultssupporting
confidence: 91%
“…The MC tools, the problem's setup and the process in obtaining of the results have been introduced according to the following subsections: MC Setup. In the present evaluations, for better performance and to obtain the more reliable evaluations, two MC tools have used; MCNPX2.7 and GEANT4.10.5-p02, in which, the MCNPX utilized TENDL 2017 47,48 and GEANT4 also utilized physics lists of QGSP_BIC_HP 44,45 for the both proton and neutrons interactions introduced as follow;…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, any boron carrier agents such as boronophenylalanine have a small uptake in the tumour. The mentioned in vitro investigation 7 will not be prepared in the current study, because it was prepared by the above-mentioned study, 8 and it has a different structure than our work. However, the first group's results 1,3-5 will only be dealt on to see whether the used 11 B concentration is realistic?…”
Section: Introductionmentioning
confidence: 99%
“…However, their findings were questioned by Mazzone et al, some months later. 8 Mazzone et al performed some MC calculations by GEANT4 9 and, consequently, indicated that the results cannot demonstrate the dose enhancement for the in vitro setup because the yield of alpha particles is too low to affect the proton therapy dose. In addition, any boron carrier agents such as boronophenylalanine have a small uptake in the tumour.…”
Section: Introductionmentioning
confidence: 99%